Kemampuan Perencangan Kota Dalam Memecahkan Persoalan Perkotaan - Zulkaidi, Denny (Journal of Regional and City Planning, 2003)
One of significant of urban design is its capability to solve urban problems through creative design. However, its effectiveness depends on the nature and structure of urban problems. To be aware of the probability of urban design in solving urban problems, urban designer, therefore, should understand the nature and be capable in structuring urban problems using the appropriate method. Design problems is certainly within the capacity of urban design to solve, while non-design problems, such as major social and political problems, are beyond the capability of urban design. Nevertheless, there is evidence that design solutions for design problems sometimes fails, particularly when dealing with unexpected social and cultural behavior of people. On the other hand, creative design to some extent are able to deal with some non-design problems at micro scale. The effectiveness of urban design in solving design and non-design urban problems is constrained by the nature of the problems, the capability of urban designers in identifying and structuring the problems, and users perceptions and behavior. To improve the effectiveness of urban design solutions in Indonesia, mass education on urban design, socialization of urban design products, regulations for design control, and consistent enforcement should be applied accordingly.Keywords: design problems, non-design problems, policy problems, problem identification, problem structuring